Karonudib is a promising anticancer therapy in hepatocellular carcinoma. (August 2019) - Hua, Xiangwei; Sanjiv, Kumar; Gad, Helge; Pham, Therese; Gokturk, Camilla; Rasti, Azita; Zhao, Zhenjun; He, Kang; Feng, Mingxuan; Zang, Yunjin; Zhang, Jianjun; Xia, Qiang; et al.
Background: Hepatocellular carcinoma (HCC) is the most common form of liver cancer and is generally caused by viral infections or consumption of mutagens, such as alcohol. While liver transplantation and hepatectomy is curative for some patients, many relapse into disease with few treatment options such as tyrosine kinase inhibitors, for example, sorafenib or lenvatinib. The need for novel systemic treatment approaches is urgent. Methods: MTH1 expression profile was first analyzed in a HCC database and MTH1 mRNA/protein level was determined in resected HCC and paired paracancerous tissues with polymerase chain reaction (PCR) and immunohistochemistry. HCC cancer cell lines were exposed in vitro to MTH1 inhibitors or depleted of MTH1 by siRNA. 8-oxoG was measured by the modified comet assay. The effect of MTH1 inhibition on tumor growth was explored in HCC xenograft in vivo models. Results: MTH1 protein level is elevated in HCC tissue compared with paracancerous liver tissue and indicates poor prognosis. The MTH1 inhibitor Karonudib (TH1579) and siRNA effectively introduce toxic oxidized nucleotides into DNA, 8-oxoG, and kill HCC cell lines in vitro . Furthermore, we demonstrate that HCC growth in a xenograft mouse model in vivo is efficiently suppressed by Karonudib. Conclusion: Altogether, these data suggest HCC relies on MTH1 for survival, which can be targeted and may open up a novel treatment option for HCC in the future.